O gênero carta do leitor em diferentes suportes e mídias: uma análise de aspectos linguístico-discursivos - Brocardo, Rosangela Oro (2015)
Inscribed in the socio-historical line and the field of Applied Linguistics (AL), this qualitative and critical-interpretative study of master's research aimed to investigate the creation and operation of the discursive genre reader's letter, of the magazine journalism, considering its circulation on different supports and medias. The theoretical and methodological foundation is sustained by the writings of Bakhtin s Circle and in research of its contemporaneous interlocutors (ACOSTA-PEREIRA, 2008, 2012; BRAIT, 2006, 2012; FARACO, 2009; RODRIGUES, 2001, 2005), in the field that, given its particularities, is conventionally to be called Dialogic Discourse Analysis (DDA). Considering the methodological order (BAKHTIN / VOLOSHINOV 2012 [1929]), the question that moves this research is: what factors determine the constitution and the functioning of the reader's letter on different supports and medias? To clarify this question, in pursuit of the analysis of dialogical relations that are established through this genre, we select the discursive genre reader's letter as the theme, seeking to expand our knowledge of their social role, its context of production, its compositional organization and its style, casting a look also to the influences of print and digital support. As for the research data and its boundaries, we selected as object, 38 reader's letters published in different supports of Veja magazine, referring to two articles of Lya Luft published in April 2013. The methodology and data presentation are based on Rodrigues (2001), which proposes the analysis of the genre from two articulated categories: the social dimension and the verbal dimension. On the social dimension of the reader's letter, we consider relevant the specificities of the journalism social sphere, especially the particularities of one of its segments, the magazine journalism. Mediated by the journalistic sphere, the situations of discursive interaction occurred through this genre, in the two versions of the magazine, are established between reader and article writers, and among readers of Veja magazine. As to the authorship, in the case of letters published in the printed magazine Veja, there is a relationship of co-authorship between reader and editor. In the online version, the author of the letters is the web surfer reader. Furthermore, when analyzing the reader's letter in different supports and medias, we observed that they present guidelines for different partners in one and in another situation. While on the printed version of Veja, the statements are directed to the editor, the columnist and the reading public, in the version published in the internet, the possibilities for interlocution are enlarged. The speakers, when interacting through this genre at online Veja, can address to, at any time, the general reader public of the magazine, as for more specific audiences, the other columnists, etc. As for the verbal dimension, we analyzed, firstly, the object of discourse of the 9 reader's letter, which is composed by the marking of an axiological position of the readers regarding aspects related to contemporary education and violence. We verified that the purpose of this genre consists on the development of a speaker's reaction-response, which seeks to take a position regarding the themes, having as immediate motivator event the articles by Lya Luft about these issues. On their reactions-response the readers have different evaluative positions of the theme, sometimes challenging it, sometimes exalting it. We verified also that this genre presents different stylistic and compositional regularities in each support and media. For example, in the printed version of the magazine, possibly due to its editing process, we found the preference for the standard cultural norms on the reader's letters, while on the online versions, present a strong tendency to the informal use of language, given the greater freedom of interaction observed on this media. About the specific compositional marks of this genre in its online version, we noted as a discursive regularity the interleaving of the reader's letter with other genres, such as the comment and the propaganda. In the course of our analysis, we found that this genre is stabilized in different ways in one and another support and media. About the relation between genre-support-media, we understand, from the analysis of the dimensions of the reader's letter, the support, as a media element, is not the component that most directly relates to genre. In the process of interaction that situates the reader's letters in study, we observed that it is the media that exerts higher determinations on the constitution and functioning of this genre, not the support